Pengaruh Penerapan Audit Internal, Integritas Auditor terhadap Pendeteksian Kecurangan dan Penyalahgunaan Wewenang - Poppy Damayanti; Hapzi Ali (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
The effect of The Implementation of Internal Audit, Auditor Integrity, on The Detection of Fraud and Abuse of Authority is a scientific article in the literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method with the research library comes from e-books and open access e-journals. The results of this article: 1) The Implementation of Internal Audit has an effect  on The Detection of Fraud and Abuse of Authority; 2) Auditor Integrity has an effect  on The Detection of Fraud and Abuse of Authority.